Designing and studying a food diary application to explore environmental awareness - Kalupahana Liyanage, Nuwanjith Bettans De Silva (2013)
A study was conducted to attempt to determine the capabilities of a computing application to raise people awareness regarding the environmental impact of food. For this purpose a diary application was developed that recorded and then estimated the impact of food that users consumed. The impact was expressed in the form of greenhouse gas emissions that are related to food products. The greenhouse gases related to food products was estimated on a separate study using a methodology known as Life-Cycle Analysis. After participants were recruited, their level of awareness and concern about the environment was determined using a questionnaire. This was done prior to the commencement of the diary study. The participants used the diary application for an average of 10 days. The application was able generate and then present textual, numeric and graphical feedback to the participants depending on the foods they consumed during the study in an attempt to raise their awareness about the environmental impact of food. The application was also used to raise the participant’s awareness on the environment and climate science. After the conclusion of the diary study the participants completed a post-study questionnaire and took part in an exit interview. The post-study questionnaire was used to asses any possible changes in awareness, concern and knowledge among the participants. The interview was used to explore a range of themes relating to the study. The findings of the study suggest that it may be possible to raise people's awareness on certain environmental issues by the short-term use of an computing application. However it appears that it is unlikely people would be able to gain detailed/in-depth knowledge on a certain subject matter by using a computing application for a short period of time. The usability analysis indicates that the diary application is very usable. The findings also suggest that incorporating competitive aspects to applications could possibly lead users to become highly motivated to accomplish certain tasks.